ANALISIS ELASTISITAS PRODUKSI PADI DI PROVINSI JAWA TIMUR TAHUN 2007-2015 - Pradityo Fahril Arrahman; Idah Zuhroh (Jurnal Ilmu Ekonomi JIE, 2020)
The purpose of this study is (1) to find out how the effect of land area and labor of the agricultural sector on rice production in East Java Districts and (2) to find out how the differences between productivity strata are related to the influence of agricultural land area and labor on rice production in Districts in East Java Province. The analytical tool used is panel data regression which is then tested by hypothesis F test, t test and coefficient of determination (R2) at the error rate α = 5%. The results of panel data regression with the selected model are Fixed Effect Model showing that the area of land has a positive and not significant effect on rice production with a value of 0.08 and labor has a significant negative effect on rice production with a value of -0.31. While the coefficient of determination (R2) is 0.94 or 94%. Conclusion for East Java, the highest production strata, medium production strata and low strata production coefficient values of land area and labor variables show less than 1, which means inelastic to rice production.